Towards quantifying exfiltration from in situ sanitary sewer pipes - Griffith, John F.; Steele, Joshua A.; Gonzalez-Fernández, Adriana; Schiff, Kenneth C. (Frontiers in Environmental Science, 2025)
Exfiltration from sanitary sewers has been researched for many years because of its potential impact on shallow groundwater or surface water, but measurements of exfiltration in situ are rare. Most previous measurements of sanitary sewer exfiltration have been done in the laboratory, in the field using natural, chemical or pharmaceutical tracers or modeled. Relatively few studies have employed physical measurements of volume loss in field settings. Here, we design, test, and apply at a watershed scale, a new methodology for measuring volume loss from sanitary sewer pipes that are currently in use and under typical operating conditions (i.e., not pressurized). The measurement system works by: (1) isolating a section of sanitary sewer between maintenance holes using a sewer bypass or equivalent, (2) introducing roughly 4,200 L of water at a controlled rate into the upstream inspection hole so that pipes remain one-third to one-half full, (3) using vacuum pumps to recover the introduced water at the downstream inspection hole, then (4) measuring differences in the volume from what was pumped into the inspection hole to what was recovered. This process is repeated up to six times to achieve a sensitivity of 0.95 L per experimental pipe segment. This technique was applied to 23 pipe segments of various ages and materials of construction that were selected to be a representative sample of the pipes throughout San Diego. Collectively, these pipes averaged averaged 3.78 × 10−2 L/s-km exfiltration rates (95%CI: 4.96 × 10−2, 2.60 × 10−2). Two of the pipe segments were infiltrating groundwater. Six pipe segments were not statistically different from zero (i.e., no exfiltration). There was no statistical difference between pipe segments of differing ages (p = 0.5) or materials of construction (p = 0.3). This study represents an initial effort at measuring exfiltration from in situ sanitary pipes. Future applications of this methodology should focus on method optimization, measurements at additional locations, and expanding measurements to collect data from additional types of pipe to better understand the geographic portability of the method and the relationship between exfiltration rates, pipe material, and pipe age.